Spatial decision-making model for priority development of Indonesia coast guard stations - Adiatmaja, Novianto Hary; Septiani, Winnie; Dewayana, Triwulandari Satitidjati; Luis, Martino (Universitas Mercu Buana, 2025)
Indonesia Coast Guard (IDNCG) is a paramilitary agency in charge of security and safety patrols in Indonesian maritime waters. The research objective is to develop priorities for the development of 35 IDNCG stations are expected to be constructed within 3 years and are considered priority project to face the increasing threats at sea. However, there is presently no system to provide support for the scientific solutions to prioritize station development despite the need for immediate decisions. This research was used to design model for determining station development priorities using the integration method of Geographic Information Systems (GIS), Analytical Hierarchy Process (AHP), and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). GIS was used as an effective tool for identifying and taking measurements in certain areas. Meanwhile, multi-criteria decision-making (MCDM) methods such as AHP and TOPSIS provided structural and pairwise quantification, as well as comparisons between elements and criteria for ranking station construction priorities. The most suitable alternative stations to be prioritized were determined by integrating the three methods which were classified as cost-effective for decision-making. Model was based on four criteria, including distance to Archipelagic Sea Lanes (ASL), Distance to the port, vulnerability coverage, and vessel density coverage. Stations were ranked based on a three-year development plan. The location ranking is then expressed in the form of a map to be used by policy makers in determining priorities for developing IDNCG Stations which will have an impact on increasing security and safety in Indonesian waters.